2021
DOI: 10.2147/cia.s310405
|View full text |Cite
|
Sign up to set email alerts
|

Sociological Narrative of Suicidal Behavior Among Older People

Abstract: Background: Globally, suicide is regarded as an immoral behavior and can be considered a criminal act in some societies. Sociological narrative views suicide not only as a result of mental illness suffered by the individuals but may also be caused by the social environment and other risk factors. Purpose: The objective of this study is to examine the social risk factors that drive older people to have suicidal feelings or tendencies and the extent to which these factors arise from the changes that occur in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 31 publications
(52 reference statements)
0
9
0
Order By: Relevance
“…The studies identified were published between 2009 and 2021. There were seven studies conducted in three countries, four from Taiwan ( 23–25 , 32 ), two from South Korea ( 19 , 20 ) and one from Malaysia ( 33 ). The total sample size was 177 participants all aged over 60 years of age.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The studies identified were published between 2009 and 2021. There were seven studies conducted in three countries, four from Taiwan ( 23–25 , 32 ), two from South Korea ( 19 , 20 ) and one from Malaysia ( 33 ). The total sample size was 177 participants all aged over 60 years of age.…”
Section: Resultsmentioning
confidence: 99%
“…The settings varied between studies with two being conducted in veterans homes ( 25 , 32 ), three in psychiatric out-patient clinics ( 20 , 23 , 24 ), one in a long term care hospital ( 19 ) and one in the home environment ( 33 ). All of the studies included used a variety or recognized qualitative research designs to data collection and data analysis – two used descriptive phenomenology ( 19 , 25 ), three used content analysis ( 20 , 23 , 24 ) and two used thematic analysis ( 32 , 33 ). Individual interviews were the preferred approach to data collection in all studies ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations